Ответ:
Объяснение:
!!!!!!!!!!!!!!!!!!!!!!!!
надо подставлять числа вместо переменной
a(1) = 2
a(n + 1) = -2a(n)
n = 1
a(2) = a(1+1) = - 2a(1) = -2*2 = -4
n = 2
a(3) = a(2+1) = -2a(2) = -2*(-4) = 8
n = 3
a(4) = a(3 + 1) = -2a(3) = -2*8 = -16
n = 4
a(5) = a(4 + 1) = -2a(4) = -2*(-16) = 32
итд
ответ 2. -4, 8. -16, 32 .....
Copyright © 2025 SCHOLAR.TIPS - All rights reserved.
Answers & Comments
Verified answer
Ответ:
Объяснение:
!!!!!!!!!!!!!!!!!!!!!!!!
Verified answer
надо подставлять числа вместо переменной
a(1) = 2
a(n + 1) = -2a(n)
n = 1
a(2) = a(1+1) = - 2a(1) = -2*2 = -4
n = 2
a(3) = a(2+1) = -2a(2) = -2*(-4) = 8
n = 3
a(4) = a(3 + 1) = -2a(3) = -2*8 = -16
n = 4
a(5) = a(4 + 1) = -2a(4) = -2*(-16) = 32
итд
ответ 2. -4, 8. -16, 32 .....